Involvement of gelsolin in TGF-beta 1 induced epithelial to mesenchymal transition in breast cancer cells - Chen, Zhi-Yuan (J Biomed Sci, 2015)
BACKGROUND: Increasing evidence suggests that transforming growth factor-beta 1 (TGF-β1) triggers epithelial to mesenchymal transition (EMT) and facilitates breast cancer stem cell differentiation. Gelsolin (GSN) is a ubiquitous actin filament-severing protein. However, the relationship between the expression level of GSN and the TGF-β signaling for EMT progression in breast cancer cells is not clear. RESULTS: TGF-β1 acted on MDA-MB231 breast cancer cells by decreasing cell proliferation, changing cell morphology to a fibroblast-like shape, increasing expressions for CD44 and GSN, and increasing EMT expression and cell migration/invasion. Study with GSN overexpression (GSN op) in both MDA-MB231 and MCF-7 cells demonstrated that increased GSN expression resulted in alterations of cell proliferation and cell cycle progression, modification of the actin filament assembly associated with altering cell surface elasticity and cell detachment in these breast cancer cells. In addition, increased cell migration was found in GSN op MDA-MB231 cells. Studies with GSN op and silencing by small interfering RNA verified that GSN could modulate the expression of vimentin. Sorted by flow cytometry, TGF-β1 increased subpopulation of CD44+/CD22- cells increasing their expressions for GSN, Nanog, Sox2, Oct4, N-cadherin, and vimentin but decreasing the E-cadherin expression. Methylation specific PCR analysis revealed that TGF-β1 decreased 50 % methylation but increased 3-fold unmethylation on the GSN promoter in CD44+/CD22- cells. Two DNA methyltransferases, DNMT1and DNMT3B were also inhibited by TGF-β1. CONCLUSIONS: TGF-β1 induced epigenetic modification of GSN could alter the EMT process in breast cancer cells.